134 Reliability and Usability of Step Sensing System on Gait Speed and Stepping Accuracy Measurement: A Preliminary Evaluation - Panas Jesadaporn; Yudh Jayapravitra; Piyapong Khumrin (My University, 2019)
Abstract Background Falls are the most common cause of injury among older people in Thailand. However, there are no established falls prevention programs in our community. Telehealth is one of the strategies to overcome this unmet need. We have developed the Step Sensing System (SSS) for measuring gait speed and stepping accuracy of multi target stepping task (MTST). This system comprises of the footstep sensing modules, controller box and analyzing computer. SSS records each footfall and compares with an assignment for each walking trail. The results will be sent to a cloud storage which are accessible by web-based and mobile applications. By using this technology, we are able to remotely access falls risk and monitor MTST performance in older people. Methods We placed footstep sensing modules under a 6-metre mat, then asked a 32-year-old healthy woman to walk across the mat for 4 trails: usual-pace, faster-pace, usual-pace with 1 assigned target and usual-pace with 2 assigned targets on an alternating sequence. We evaluated the system reliability by comparing gait speed and stepping accuracy on 3rd and 4th trails with video recorded by Intel RealsenseTM Depth Camera (model D415). Results SSS and video recording has excellent correlation for gait speed and stepping accuracy measurement (intraclass correlation coefficient [ICC] > 0.99, p value < 0.001). The user satisfaction measured by the System Usability Scale was 70/100. Conclusions SSS demonstrated promising results on gait speed and stepping accuracy measurement in controlled environment. For the next step, we plan to increase ability of gait measurement on various parameters and perform the validity assessment in community setting.
Keywords: Pace; Diabetic Foot Ulcer Assessment and Management